What is Safe about Safe Sport? A Gendered Interrogation of Canadian University Safe Sport Policies in Higher Education - Baker, Hayley; Gardiner, Rita; Egan, Kasey (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2025)
In this paper, we seek to examine how organizational norms and structures in Canadian university sport perpetuate a culture that does not adequately address maltreatment, harassment, and abuse that affects women athletes. Our examination focuses on two inter-related questions. First, how do safe sport policies highlight gendering practices in university athletics? And second, how is safety problematized in safe sport policies? In addressing our research question, we apply genderwashing as a conceptual framework, alongside Carol Bacchi’s “What’s the Problem” approach to analyze the USPORTS and Western University’s safe sport policies. Our analysis reveals that safe sport policies demonstrate genderwashing practices in their use of gender-neutral language. The use of gender-neutral language within these policies contributes to an erasure of women athletes’ experiences, and a reluctance to engage with issues of gender violence in sport. We suggest addressing this issue will require a commitment to creating a safe sport culture that recognizes gender, and other axis of identity, as relevant to athletes’ diverse experiences and understanding of safety within Canadian university sport.